Agricultural Sector and Processing Industry Sector Implications: Increasing Economic Growth - Nurcayah Nurcayah; Asriani Asriani; Wa Embe (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Regional development based on the region's potential, condition, and characteristics will increase regional competitiveness and economic growth. This study determines the advantages of agricultural and manufacturing sectors to support economic growth in Southeast Sulawesi Province. Using descriptive-quantitative analysis, this research data are GRDP values of 12 (twelve) Regencies/Cities in Southeast Sulawesi Province in 2016-2021. The analysis model used is the analysis of LQ, DLQ, and MRP methods. The results of the study found that the agricultural sector in regencies/cities except Kendari City plays a leading industry, meaning that it makes the most significant contribution to economic growth but has slow growth because the productivity of agricultural products decreases from year to year. The manufacturing sector in regencies/cities is a non-base sector, and change is not dominant, so it has a low contribution to the economic growth of regencies/cities and Southeast Sulawesi Province, except for the Konawe Regency. The manufacturing sector in Southeast Sulawesi had a soft gift because it is dominated by the food and beverage industry with low production value, resulting in slow growth. Competitiveness-based development policies according to regional potential will encourage the performance of all economic sectors. Programs to increase agricultural productivity, the primary industry, boost economic growth, and support added value in the manufacturing sector.